Design of industrial robot performance testing device based on ECMA servo motor and PLC control software - Xue Hou (ROBOMECH Journal)
Abstract With the rapid development of science and technology, various types of industrial robots occupy an important role in industrial production. Therefore, the performance testing of industrial robots is very important. In response to the low accuracy in performance testing of industrial robots operating under extreme working conditions using traditional testing devices, a performance testing device for industrial robots is designed using a dedicated servo motor model and programmable logic controller. To test the proposed testing device, comparative experiments are conducted. The results showed that when the temperature varied between − 40 ℃ and 80 ℃, the motor operating speed of the proposed device was around − 2,993 r/min, which was better than the comparative device. It was not significantly affected by temperature. Under over-speed conditions of 1.0 times, 1.2 times, 1.4 times, and 1.6 times, the motor temperatures of the proposed device after operating 20 min were 36 ℃, 40 ℃, 45 ℃, and 53 ℃, respectively, which were significantly lower than those of the comparative device. In summary, the proposed industrial robot performance testing device based on ECMA servo motor and PLC can maintain a stable state under extreme conditions, providing an appropriate idea for the performance testing of industrial robots and ensuring a guarantee for the design of industrial robots.